Japanese table furniture - Mustapa, Imran; Ismail, Izwan; Ahmad, Zainul Ariffin (2010)
This project was conducted by final semester students of Diploma in Wood Industry. The objectives of this study are to solve the problem that usually happened in limited space of living room. Inspired by that, the Japanese table with bookshelf at the side designed to save space and then to fulfill the demand which come with attractive characteristic such as modern, simple, and multi function. Currently people more interest to simple and multi function furniture in their home so that it looks practically and modem. So the Japanese Table was created based on the survey that already taken. Many factors that influent to the demand included the color which is one of the important factors to attract people to buy the furniture and also the design for the furniture. So this project has been done follow on what the design that people are looking for today especially Japanese. They were interested more on finger joint design and bright color.